The Analysis of Writing Format and Abstract Structure of Dissertation Written by Ph.D Students of State Universities, Surabaya - Sukirmiyadi; Erwan Adi Saputro; Susilowati; Silvana Dwi Nurherdiana (Technium Social Sciences Journal, 2023)
As one of the most important part in one research, an abstract should be written as well as possible to make the readers be capable of comprehending and assessing whether its quality is good or not. Based on Koopman (1997: 1) and Owen D Williamson (2007: 3) that one of the criteria of good abstract is that it should have the complete abstract structure, that is Introduction, Objective or Aim, Methodology, Findings/Results and Conclusion written within 5 (five) paragraphs. In fact, not all abstract written by Ph.D students have those 5 (five) aspects and format. Referring to the problem stated above, this research is aimed at finding and describing some variations of writing format and abstract structure written by Ph.D students of State Universities in Surabaya. Meanwhile, the methodology employed in this research was descriptive qualitative. The data were taken from 15 dissertation abstracts written by Ph.D Students: 8 abstracts taken from the Faculty of Civil Engineering and Planning/FTSP-ITS and the 7 others were from Medical Science of Airlangga University Surabaya. The data collected were the writing format dealing with the number of paragraphs of each abstract and its abstract structure. Furthermore, having been analyzed and discussed, among those 15 abstract texts, it was found that the writing format and its variations of abstract structure of dissertation was: [a] in accordance with the number of paragraphs: 6 texts (40%) written in 3 paragraphs, 4 texts (26,66%) written in 5 paragraphs, 3 abstracts (20%) written in 4 paragraphs, 2 texts (13,33%) written in 1 paragraph; [b] Meanwhile in accordance with the number of abstract structures: most of the abstracts: 9 abstract texts (60%) were not completed with ‘conclusion‘, 5 texts (33,33%) with no ‘objective‘, only 4 texts (26,66%) were completed with 5 abstract structure, 4 texts (26,66%) were not supported with the 2 abstract structure: ‘objective and conclusion‘ and 1 text (6,66%) did not have an ‘introduction‘. Finally, it was found that there were several variations dealing with the writing format of dissertation abstracts both in line with the number of paragraphs and and its abstract stucture. You should leave 8 mm of space above the abstract and 10 mm after the abstract. The heading Abstract should be typed in bold 9-point Arial. The body of the abstract should be typed in normal 9-point Times in a single paragraph, immediately following the heading. The text should be set to 1 line spacing. The abstract should be centred across the page, indented 17 mm from the left and right page margins and justified. It should not normally exceed 200 words.